Macular hole surgery with short-acting gas and short-duration face-down positioning - Xirou T (Dove Medical Press, 2012)
Tina Xirou,1 Panagiotis G Theodossiadis,2 Michael Apostolopoulos,3 A Stamatina Kabanarou,1 Elias Feretis,1 Ioannis D Ladas,3 Chrysanthi Koutsandrea31Vitreoretinal Unit, Red Cross Hospital, 2B Department of Ophthalmology, University of Athens, Greece; 3A Department of Ophthalmology, University of Athens, GreecePurpose: To report on the outcomes of vitrectomy and sulfur hexafluoride (SF6) gas tamponade for idiopathic macular holes with 2 days of face-down positioning.Patients and methods: This was a prospective, nonrandomized, observational sequential case-series study on 23 consecutive patients receiving macular hole surgery using 20% SF6 and advised to stay in a face-down position for 2 days postoperatively (SF6 group). These patients were compared to 23 consecutive patients who had previously undergone macular hole surgery, had received 14% C3F8, and were advised to maintain a face-down position for 2 days (C3F8 group). Patients in both groups underwent vitrectomy, internal limiting membrane peeling, and fluid gas exchange using either SF6 or C3F8. Preoperative and postoperative data included best corrected visual acuity recorded in LogMAR units, slit-lamp biomicroscopy, and optical coherence tomography.Results: At a 6-month follow-up, macular hole closure was noted in 23/23 eyes (100%) and in 22/23 eyes (96%) in the SF6 and C3F8 groups, respectively. The improvement in visual acuity (measured through Snellen acuity lines both preoperatively until 6 months postoperatively) was 4.08 ± 2.31 (95% confidence interval [CI]: 3.08–5.08) for the SF6 group and 2.87 ± 2.30 (95% CI: 1.87–3.86) for the C3F8 group; this difference was not statistically significant (P = 0.06).Conclusion: Vitrectomy with internal limiting membrane peeling and a short-acting gas tamponade using SF6 with posture limitation for 2 days may give a high success rate in macular hole surgery.Keywords: idiopathic macular holes, SF6 gas tamponade, C3F8 gas tamponade